Circadian clocks and adaptive immune function: from mechanisms to therapeutic applications - Szredzka, Aleksandra; Chwastowicz, Anna; Pergoł, Joanna; Matryba, Paweł (Frontiers in Immunology, 2025)
The circadian clock exerts profound regulatory control over adaptive immunity, particularly affecting T and B lymphocyte development, trafficking, activation, and effector function. These immune cells possess autonomous molecular clocks governed by core genes such as Bmal1, Clock, Per1/2, and Cry1/2, which influence transcriptional programs related to receptor expression, cytokine signaling, and metabolism. Circadian regulation shapes the daily oscillation of lymphocyte recirculation through lymphoid organs, modulates antigen responsiveness, and fine-tunes subset differentiation-most notably skewing CD4+ T cell fate toward Th1, Th2, Th17, or Treg lineages depending on time-of-day-linked signaling cascades such as mTOR/Akt and RORγt/Nfil3 pathways. Similarly, rhythmic glucocorticoid and catecholamine signaling synchronize peripheral lymphocyte clocks with systemic cues, integrating hormonal and environmental information. Clinically, circadian disruption - whether through genetic mutations, shift work, or chronic stress - has been linked to aberrant lymphocyte function, increased autoimmunity, impaired vaccine responses, and reduced immunosurveillance in cancer. Recent findings demonstrate that time-of-day-dependent administration of vaccines and immunotherapies, including checkpoint inhibitors, can significantly influence clinical efficacy and immune outcomes. Understanding the temporal orchestration of adaptive immunity thus holds translational potential for optimizing therapeutic strategies, including chronotherapy and vaccination scheduling.